P853 Human factors engineering to drive the development of a next generation colli-pee home-based first-void urine collection. (14th July 2019) - Donné, Joke; Beyers, Koen; Urlings, Judith; Rios-Cortes, Alejandra; Bossche, Ronald Van Den; Meers, Nette; Avondt, Quinten Van; Provinciael, Tine; Hochstenbach, Laura; Wauben, Paulette; Huijnen, Claire; Ceccarelli, Bianca; et al.
Abstract : Background: The first-void urine (first 20 ml of the urine flow) is being used for the detection of sexually transmitted infections (STIs), in particular for the detection of (1) Chlamydia trachomatis, (2) Neisseria gonorrhoeae, (3) Mycoplasma genitalium and (4) Trichomonas. Novosanis' Colli-Pee is an innovative device for standardized, volumetric and hygienic self-collection of first-void urine. The aim of the study was to design a next generation of the Colli-Pee device optimized in architecture and right materials for postal mailing. Methods: Co-creation sessions by living labs Happy Aging (BE) and EIZT (NL) were organized with 20 volunteers to score four 3D-printed designs. Additionally, at home-based testing allowed assessment of the usability of the new generation Colli-Pee in 120 healthy volunteers; 60 in BE and 60 in NL. Volunteers provided feedback via an online questionnaire on the ease of use, the process of an online urine self-test: from requesting and receiving the Colli-Pee urine collection system to the collection of urine to the returning of the sample by postal mail. The returned samples were checked for leakage and collected volume; as well as return conditions. Results: The prototype with a flexible funnel scored best for time of sampling (8.3), user-friendliness (8.3), and choice of material (8.6). The first results from 38 Belgian participants showed no difference between collected volume for the different pee positions used (p=0.996, Kruskal Wallis Test; mean (SD) in mL: standing position 10.21 (0.34), forward sitting position 10.00 (0.86), backward sitting position 10.34 (0.55)). From 50 Belgian participants, 20% of the volunteers mentioned that they did not use the instructions to assemble the Colli-Pee and 92% would recommend the Colli-Pee to others. Furthermore, all returned boxes with a urine sample were intact upon arrival. Conclusion: The next-generation Colli-Pee was well-accepted and offers a solution for home-based collection. Disclosure: No significant relationships.